2009
DOI: 10.1055/s-0029-1239448
|View full text |Cite
|
Sign up to set email alerts
|

Ear Reconstruction Using a Porous Polyethylene Framework and Temporoparietal Fascia Flap

Abstract: Ear reconstruction is a difficult procedure requiring a framework and soft tissue covering. The traditional method uses a rib cartilage framework placed beneath scalp skin. This method has been used for 50 years despite inherent problems with both harvesting rib cartilage and using scalp for coverage. The authors describe a method using a porous polyethylene (PPE) framework covered by a large temporoparietal fascia (TFP) flap raised with the underlying subgaleal fascia (SGF). The entire implant is covered by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
106
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(118 citation statements)
references
References 14 publications
0
106
0
4
Order By: Relevance
“…Since 2006, Romo et al, [8][9][10] Reinisch and Lewin, 11 Berghaus et al, 12 and Yang et al 13 have reported successful ear reconstruction using porous polyethylene as a substitute for rib cartilage. The polyethylene implant technique typically requires 2 or 3 stages spaced 4 months apart.…”
mentioning
confidence: 99%
“…Since 2006, Romo et al, [8][9][10] Reinisch and Lewin, 11 Berghaus et al, 12 and Yang et al 13 have reported successful ear reconstruction using porous polyethylene as a substitute for rib cartilage. The polyethylene implant technique typically requires 2 or 3 stages spaced 4 months apart.…”
mentioning
confidence: 99%
“…Sengezer et al, 1996 mentioned three exposures in 10 ear reconstruction cases which were managed without implant removal [18]. Reinisch et al 2009 reported 7% exposure rate in ear reconstruction using Porous polyethylene framework was performed on 786 cars over an 18-year period [19]. Zhao et al 2009 reported that exposure of frame were 15 (1.07%) in 1485 autogenous graft cases autogenous graft while occurred in 48 (13.5%) cases MEDPOR ® alloplastic frame [9].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of surgeons use porous polyethylene as a framework for auricular reconstruction of both congenital and acquired defects [3,23]. Porous polyethylene is a synthetic thermoplastic with a pore size of 100-200 μm, thus allowing tissue ingrowth; it can be considered the most widely used alloplastic material for ear reconstruction [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used coverage of the porous polyethylene framework is a temporoparietal fascia flap [3]. However, in this case, we chose a postauricular fascia flap to cover the framework.…”
Section: Case Presentationmentioning
confidence: 99%